Towards a topology of 'Doing Gender': an analysis of empirical research and its challenges - Nentwich, Julia C.; Kelan, Elisabeth K. (Wiley, 2014)
‘Doing gender’ is a much used term in research on gender, work and organizations. However, translating theoretical insight into empirical research is often a challenging endeavour. A lack of clarity with regard to the conceptualization and operationalization of key terms in turn often limits the theoretical and empirical purchase of a concept. The aim of this article is therefore to provide a systematization of empirical approaches to ‘doing gender’. This systematization leads to a topology of five themes that is derived from empirical research in the field. The five themes identified are structures, hierarchies, identity, flexibility and context specificity, and gradual relevance/subversion. Each theme explores a different facet of ‘doing gender’. This topology helps empirical researchers to be more specific about which aspects of ‘doing gender’ they are referring to. This in turn can help to unfold the theoretical potential of the concept of ‘doing gender’.
Keywords: (un)doing gender; identity; ethnomethodology; performativity; empirical studies